Desafios da educação crítica nas ciências agrárias: possibilidades e limites na versão Residência Agrária UFPB - vasconcelos, Gilvânia de Oliveira Silva de (2015)
This thesis was the object of study Specialization Course in Family Farming Peasant Education and Field UFPB, the National Programme for Education Planning: Students and Professional Qualification Training for Technical Assistance and Rural Extension - Agricultural Residence course, offered by the Program National Education in Agrarian Reform (PRONERA). The research aimed to investigate the concept of education and the preparation processes of (the) professional for a role in the peasant family agriculture, and specific objectives, seek to: a) conceptually to characterize the critical education; b) characterize the PRONERA as public policy to conduct the course Agrarian residence; c) To analyze the perceptions of the graduates about the educational processes of the course and its performances. The research was guided by the questions: how to conceive and develop the course professional training processes Agrarian Residence? The concepts and practices include the principles of critical education and rural education? The training enables foundation to guide the work of professionals towards the educator technical? The research, qualitative, consisted of a case study. Procedures and research tools consisted of analysis of documents and interviews with former students and teachers who worked in the course of a total of sixteen interviews. The result of this research process finds itself ready in seven chapters, and the final chapter focuses the results in more detail. Thus, we find, even occasionally, this course contributed to a critical formation and reaffirmed commitments teachers technical to strengthen a peasant family agriculture. As theoretical support, we use several authors: Prado Junior (1981); Furtado (2007); Silva (1998); Martin (1995); Jesus (2007); Demo (1996); Paiva (1987); Zotti (2004); Romanelli (1998); Saviani (2008); Fernandes and Molina (2004); Caldas (2008); Hofling (2001); Freire (1969, 1977, 1999, 2006); Caldart (2004); Brandao (1992); Gadotti (1992). The survey results show that after the course, there was a change in attitude and actions of educators Technical. All (the) respondents are working together with peasant family farming, on the NGO or field of schools with a methodology that recognizes and values the subjects.